Josephus' Contra Apionem : studies in its character and context with a Latin concordance to the portion missing in Greek - Feldman, Louis H.; Levison, John R. (Arbeiten zur Geschichte des antiken Judentums und des Urchristentums, 1996)
This volume offers a state-of-the-art collection of papers on one of the most significant works of Flavius Josephus, by many of the leading scholars in current Josephus research. The collection, which includes a concordance by H. Schreckenberg of the Latin section Contra Apionem 2.52-113, forms a standard, indispensable resource for the study of Josephus' writings, of apologetic literature in general, and particularly for the study of Contra Apionem , one of the most significant apologetic treatises in Antiquity.